Professionalism and the Expanding Horizons of the Information Profession: The Challenges Facing Librarians in the 21st Century - Entsua-Mensah, Clement (Ghana Library Journal, 2004)
Given the extent to which technological developments have influenced information work, the greatest challenge that confronts information professionals, and for that matter librarians, in the 21 st century is the threat posed by the fast moving changes that have been brought about by these emerging technologies.